(untitled) (Research, Society and Development, 2022)
COVID-19 (corona virus disease 2019) is a respiratory infection caused by SARS-COV-2 in which 14% of cases progress to severe conditions, 5% require intensive care units and 2% progress to death. The oral cavity is one of the gateways to the virus’s entry into the host. Periodontitis is the 6th most prevalent disease in the world and is a chronic inflammatory disease that affects the supporting tissues of the tooth. The scientific literature has sought evidence on a possible association between periodontitis and COVID-19. This study aims to search for information available in the literature that confirms an association between diseases. A search was performed in medline/pubmed databases with the combination of the descriptors: "periodontitis" or "periodontal disease" or "gum disease" and "COVID-19" or "SARS-COV-2" or "novel coronavirus" published between August 2021 and January 2022, in English and Portuguese. We found 67 articles, of which 20 were selected, based on title, abstract and language, only 14 studies were chosen to make up the review, according to availability of the full text on the web and type of work, prioritizing research and literature reviews. Patients with periodontitis and COVID-19 present: shared risk factors, presence of inflammatory markers in high amounts and the presence of Sars-Cov-2 in the oral cavity, evidencing the highest chances of developing severe conditions of the disease. Future studies are needed to confirm the direct association between periodontitis and COVID-19, which has not yet been fully established.